2017
DOI: 10.3233/jvr-170910
|View full text |Cite
|
Sign up to set email alerts
|

Let’s Get to Work Wisconsin: Launching youth with intellectual and developmental disabilities into the workforce

Abstract: BACKGROUND: Beginning in spring 2012, Wisconsin's Let's Get to Work (LGTW) project spent four years working with pilot school sites and state agency personnel to implement practice and policy changes designed to elevate expectations along with employment outcomes for youth with intellectual and developmental disabilities (I/DD). This need was underscored by data demonstrating inconsistent transition practices across the state in conjunction with policy obstacles hindering employment for individuals with I/DD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…These strategies include community-based employment programs that include school and VR partnerships, individualized-customized supports, data-based decision-making (Choiseul-Praslin & McConnell, 2020), IPS employment services (Noel et al, 2018), customized employment (Riesen et al, 2015), and programs that provide internship and apprenticeship opportunities for youth with disabilities, such as Project SEARCH (Schall et al, 2020) and Wisconsin’s previous Let’s Get to Work grant that aimed to improve the employment rates of youth with IDD. Employment rates increased when schools implemented evidence-based transition services (Molfenter, Hartman, Neugart, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These strategies include community-based employment programs that include school and VR partnerships, individualized-customized supports, data-based decision-making (Choiseul-Praslin & McConnell, 2020), IPS employment services (Noel et al, 2018), customized employment (Riesen et al, 2015), and programs that provide internship and apprenticeship opportunities for youth with disabilities, such as Project SEARCH (Schall et al, 2020) and Wisconsin’s previous Let’s Get to Work grant that aimed to improve the employment rates of youth with IDD. Employment rates increased when schools implemented evidence-based transition services (Molfenter, Hartman, Neugart, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Counseling individuals through the SOC is important for increasing motivation to change and ultimately achieving the desired behavior change and outcomes (Norcross et al, 2010). it is anticipated that an individual's progress through the stages will predict their future behavior, in this case, increased motivation to seek out employment opportunities (Levesque et al, 1999).…”
Section: Stages Of Change Theorymentioning
confidence: 99%
“…This, along with the misguided belief that individuals with disabilities cannot work, contributes to the comparatively high unemployment and underemployment rates for people with disabilities (Lui et al, 2010;Tremblay et al, 2004Tremblay et al, , 2006. More recently, research has demonstrated that through the use of an array of SSA work incentives, youth with disabilities can increase their income and still maintain access to services and supports including health care, thus positively impacting overall quality of life (Molfenter et al, 2017). Therefore, research on better understanding work motivation and work readiness among transition-age youth receiving SSi is important to help improve employment outcomes and progress toward achieving greater financial self-sufficiency.…”
mentioning
confidence: 99%
“…First, special educator involvement in the work experience development process may differ depending on whether or not a transition specialist is available for support. If a transition specialist is not involved, the special educator may need release time from school-based responsibilities to do work experience development in the community (Farnon-Molfenter, Hartman, Neugart, & Webb, 2017). If the school district employs a transition specialist, then the special educator's role may focus more on helping students identify work-related strengths/interests and suggesting possible work experience matches.…”
Section: Describe the Programmentioning
confidence: 99%